2005
DOI: 10.1002/ajpa.20160
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of a serial killer: Differential diagnosis of tuberculosis based on rib lesions of adult individuals from the Coimbra identified skeletal collection, Portugal

Abstract: The role of new bone formation on visceral surfaces of ribs in the diagnosis of tuberculosis (TB) in past human populations has been explored by many researchers, using both skeletal remains with known causes of death and archaeological samples. This study focuses, firstly, on adult skeletons from the Coimbra Identified Skeletal Collection in Portugal and investigates the skeletal manifestations of individuals known to have died from TB; secondly, this study focuses on the role of rib lesions in the diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
88
1
11

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 39 publications
8
88
1
11
Order By: Relevance
“…The cause of new bone formation on the visceral surfaces of ribs has been explored by many authors, with varying diagnoses being suggested. Conclusions indicate that a range of chronic pulmonary diseases could be represented, including tuberculosis (TB), lung cancer, chronic bronchitis and pneumonia (Lambert, 2002;Roberts, 1999;Roberts et al, 1994;Santos and Roberts, 2006). The bone changes are not pathognomonic for any one condition.…”
mentioning
confidence: 99%
“…The cause of new bone formation on the visceral surfaces of ribs has been explored by many authors, with varying diagnoses being suggested. Conclusions indicate that a range of chronic pulmonary diseases could be represented, including tuberculosis (TB), lung cancer, chronic bronchitis and pneumonia (Lambert, 2002;Roberts, 1999;Roberts et al, 1994;Santos and Roberts, 2006). The bone changes are not pathognomonic for any one condition.…”
mentioning
confidence: 99%
“…This condition can be traced by the macroscopic observations of the rib cage that shows new bone formation on the visceral surface. This type of bone alteration is commonly associated with pulmonary tuberculosis (Kelley and Micozzi, 1984; 1994; Santos and Roberts, 2001;Matos and Santos, 2006), and will not be explored in this work since it has already been discussed in other publications (Santos, 2000;Santos and Roberts, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although not pathognomonic of TB, a clear correlation has been shown between rib lesions and TB, with reported incidences of up to 91%. 34 It was found that 8.8% of individuals with pulmonary TB in the Hamman-Todd Collection had lesions on the visceral side of their ribs, 35 but this figure was much higher at 61.6% in Terry Collection individuals. 36 Other reported figures for rib involvement are 85.2% (Coimbra), 34 28.0% (Ute Mountain sample), 37 2.0% (Aymyrlyg Cemetery complex) 38 and 1.0% (Wharram Percy village in northeast England).…”
Section: Introductionmentioning
confidence: 95%
“…34 It was found that 8.8% of individuals with pulmonary TB in the Hamman-Todd Collection had lesions on the visceral side of their ribs, 35 but this figure was much higher at 61.6% in Terry Collection individuals. 36 Other reported figures for rib involvement are 85.2% (Coimbra), 34 28.0% (Ute Mountain sample), 37 2.0% (Aymyrlyg Cemetery complex) 38 and 1.0% (Wharram Percy village in northeast England). 33 Conversely, of individuals with rib lesions in the Coimbra Collection in Portugal, 85.7% had pulmonary or non-pulmonary TB as cause of death, whereas 17.8% of individuals with lesions had other causes of death.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation